Changes in Agriculture in 26 Developing Nations, 1948 to 1963 - United States (Washington: Economic Research Service, U. S. Dept. of Agriculture, 1965)
The agricultural problems of 26 developing countries are considered; 7 of these countries are in Latin America, 4 in Africa, 4 in Europe, 7 in the Near East and South Asia, and 4 in the Far East. The objectives of this report is to show levels and changes since 1948 in agricultural output and productivity in these countries and to identify and assess roles of major physical, economic, and social factors associated with differences in these levels and changes.
ne 13/03/2018
Loans
Keywords: Agriculture; Developing Countries